Serological biomarkers in triage of FIT-positive subjects?. (3rd July 2017) - Nielsen, Hans J.; Christensen, Ib Jarle; Andersen, Berit; Rasmussen, Morten; Friis-Hansen, Lennart J.; Bygott, Thomas; MiCallef, Jake
Abstract: FIT-based colorectal cancer screening has been implemented in many countries including Denmark, where 916 colorectal cancer and 4468 high- or medium-risk adenoma patients were identified within April–December 2014, among 16, 806 subjects with a positive FIT test. Screening increases the overall requirements for colonoscopy, which may challenge the current capacity. Some countries have increased their initial FIT cut-off level in order to comply with lack of colonoscopy capacity. Many patients with neoplasia will not be detected, however, by using increased FIT cut-off levels. The number of patients with neoplastic lesions missed by increased cut-off levels appears to be much higher than expected. Therefore, tests that identify those patients missed by increased FIT cut-off levels must be developed. Preliminary results of determination of one of several biomarker entities currently under investigation show that nucleosome blood tests may be one option for identifying some of these patients. Implementation of a triage test consisting of FIT, blood-based biomarkers and plus/minus colonoscopy is suggested to identify subjects with FIT levels between the initial and the increased cut-off level that must be offered colonoscopy. In addition, triage may reduce the frequency of unnecessary colonoscopies by 25%.